2018
DOI: 10.4103/ijp.ijp_36_17
|View full text |Cite
|
Sign up to set email alerts
|

In silico approach to study the metabolism and biological activities of oligomeric proanthocyanidin complexes

Abstract: OBJECTIVES:Over the past three decades, numerous studies have focused on the biological activities of oligomeric proanthocyanidins (OPCs) in the prevention of many diseases such as neurodegeneration, atherosclerosis, tumorigenesis, and microbial infections. OPC has redox-active metabolites which could modulate the intracellular redox equilibrium to maintain the antioxidant homeostasis. This redox-modulating efficiency of OPC could provide new insights into therapeutic approaches that could reduce the burden of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The criteria of the Lipinski's rule of five are as follows: logP ≤5, MW ≤500 Da, n-ON ≤10, and n-OHNH ≤5 (38). In addition, the topological polar surface area (TPSA) value is a key indicator for evaluating and predicting the oral bioavailability of molecular compounds, and the TPSA value of ≤140 Å represents good oral bioavailability (37,(62)(63)(64). %ABS value calculated according to TPSA value between 67% and 83% means an ideal oral bioavailability (37,(62)(63)(64).…”
Section: Analysis Of the Physicochemical Properties Of Luteolinmentioning
confidence: 99%
See 4 more Smart Citations
“…The criteria of the Lipinski's rule of five are as follows: logP ≤5, MW ≤500 Da, n-ON ≤10, and n-OHNH ≤5 (38). In addition, the topological polar surface area (TPSA) value is a key indicator for evaluating and predicting the oral bioavailability of molecular compounds, and the TPSA value of ≤140 Å represents good oral bioavailability (37,(62)(63)(64). %ABS value calculated according to TPSA value between 67% and 83% means an ideal oral bioavailability (37,(62)(63)(64).…”
Section: Analysis Of the Physicochemical Properties Of Luteolinmentioning
confidence: 99%
“…In addition, the topological polar surface area (TPSA) value is a key indicator for evaluating and predicting the oral bioavailability of molecular compounds, and the TPSA value of ≤140 Å represents good oral bioavailability (37,(62)(63)(64). %ABS value calculated according to TPSA value between 67% and 83% means an ideal oral bioavailability (37,(62)(63)(64). Surprisingly, the results showed that luteolin met the criteria of logP = 1.97 < 5, MW = 286.24 < 500 Da, n-ON = 6 < 10, and n-OHNH = 4 <5, and the value of TPSA at 111.12 Å < 140 and %ABS at 70.66 that ranged from 57.95% to 78.98% were at the range of ideal oral bioavailability as shown in Table 1.…”
Section: Analysis Of the Physicochemical Properties Of Luteolinmentioning
confidence: 99%
See 3 more Smart Citations